Alterations of optic tract and retinal structure in patients after thalamic stroke - Ye, Chen; Kwapong, William Robert; Tao, Wendan; Lu, Kun; Pan, Ruosu; Wang, Anmo; Liu, Junfeng; Liu, Ming; Wu, Bo (Frontiers in Aging Neuroscience, 2022)
Objectives: To investigate the association between degeneration of retinal structure and shrinkage of the optic tract in patients after thalamic stroke. Methods: Patients with unilateral thalamic stroke were included. Structural magnetic resonance imaging (MRI) and optical coherence tomography (OCT) were performed to obtain parameters of optic tract shrinkage (lateral index) and retina structural thickness (retinal nerve fiber layer, RNFL; peripapillary retinal nerve fiber layer, pRNFL; ganglion cell-inner plexiform layer, GCIP), respectively. Visual acuity (VA) examination under illumination was conducted using Snellen charts and then converted to the logarithm of the minimum angle of resolution (LogMAR). We investigated the association between LI and OCT parameters and their relationships with VA. Results:A total of 33 patients and 23 age-sex matched stroke-free healthy controls were finally enrolled. Thalamic stroke patients showed altered LI compared with control participants (P = 0.011) and significantly increased value of LI in subgroup of disease duration more than 6 months (0.031 [0.01 vs 0.002, P =0.004). In these patients, LI were significantly associated with pRNFL thickness(β = 0.349, 95% confidence interval [CI] 0.134 to 0.564, P = 0.002) after adjusting for confounders(age, sex, hypertension, diabetes, dyslipidemia, and lesion volume). LI and pRNFL were both significantly associated with VA in all patients(LI: β = -0.275, 95% CI -0.539 to -0.011, P = 0.041; pRNFL: β = -0.023, 95% CI -0.046 to -0.001, P = 0.040) and in subgroup of duration more than 6 months(LI: β = -0.290, 95% CI -0.469 to -0.111, P = 0.002; pRNFL: β = -0.041, 95% CI --0.065 to -0.017, P = 0.003). Conclusion: Shrinkage of the optic tract can be detected in thalamic stroke patients, especially after 6 months of stroke onset. In these patients, the extent of optic tract atrophy is associated with pRNFL thickness and they are both related to visual acuity changes.